The Influence of Integrated Marketing Communication Strategies on Enhancing the Adoption of GoPaylater Services - Purba, Ade Rasinta Herli Kristiani; Syahlina, Maya; Wulandari, Poppy (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2025)
The development of financial technology in Indonesia has driven innovation in digital payment services, one of which is GoPaylater, developed by Gojek. This study aims to analyze the influence of integrated marketing communication (IMC) elements on the increase in the number of GoPaylater users. A quantitative approach was employed through a survey method involving 120 active users of the Gojek application in the city of Medan. The analysis results indicate that the elements of digital advertising, sales promotion, public relations, content marketing, and social media significantly influence the decision to use GoPaylater. The combination of digital advertising and sales promotion was found to be the most effective strategy in encouraging service adoption. These findings underscore the importance of implementing an integrated marketing communication strategy to enhance brand awareness, purchase intention, and consumer trust in paylater services. This study also identifies challenges in the implementation of IMC, such as the need to maintain message consistency across various communication channels. Strategic recommendations include increasing consumer education, optimizing promotional programs, strengthening public relations, maximizing the use of social media, and leveraging data-driven analysis to better understand user behavior. The results of this study are expected to serve as a reference for the development of digital marketing strategies in the financial services sector in Indonesia.